Aplikasi Perhitungan Penyusutan Inventaris Barang menggunakan Decreasing Charge Method Berbasis Website - Yudha Sansena; Samsudin Samsudin (Universitas Hamzanwadi, 2023)
The Fajar Sejahtera Indonesia Foundation is a non-governmental social organization that has assets in four districts in the city of Medan. However, every asset in the form of goods experiences a decrease in value each year. Calculating depreciation for purchasing planning is still difficult as it is done manually on paper. The research objective is to create an asset depreciation financing application using the decreasing charge method based on a website. The programming is done using PHP, MySQL, XAMPP, and Visual Studio Code, employing the research and development method, including potential and problem identification, data collection, product design, design validation, design revision, product testing, product revision, usage testing, final product revision, and mass production. However, this research is limited to the product testing phase. Data collection techniques involve interviews, observations, and literature reviews. The system is tested using a validation test divided into three parts: expert validation, field testing, and user testing. Our findings resulted in a web-based application for calculating inventory depreciation. The expert validation test yielded a score of 3.8, indicating high validity; the field testing resulted in a score of 4.0, indicating high validity; and the user testing with five participants achieved a score of 83.2%, indicating high effectiveness.